Universal Newborn Screening for Severe Combined Immunodeficiency (SCID) - van der Burg, Mirjam; Mahlaoui, Nizar; Gaspar, Hubert Bobby; Pai, Sung-Yun (Frontiers in Pediatrics, 2019)
Patients with severe combined immunodeficiency (SCID) are born with profound deficiency of functional T-lymphocytes. Early detection and diagnosis would allow for prompt institution of isolation from infection and referral for definitive treatment with allogeneic hematopoietic stem cell transplantation. Universal newborn screening for SCID, using an assay to detect T-cell receptor excision circles (TREC) in dried blood spots, is now being performed in all states in the United States. In this review, we discuss the development and outcomes of TREC screening, and continued challenges to implementation.